Position of the Turkish national community in Kosovo-Metohia since Rambouillet and Paris talks, and KFOR and UNMIK arrival in that South Serbia's region - Kurejsh Zeynelabidin (Zbornik Radova: Geografski institut "Jovan Cvijić", 2002)
nema